Effects of gender norms on food security and asset acquisition among cassava value chain actors in Oyo and Ogun States, Nigeria - Adeagbo, D.R. (Obafemi Awolowo University, 2024)
This study identified the gender norms that were common among cassava value chain actors in Oyo and Ogun States, Nigeria; examined food security and asset acquisition among the cassava value chain actors; and determined the effect of gender norms on food security and asset acquisition among the cassava value chain actors. These were with a view to providing additional empirical information on specific gender norms, and their effect on food security and asset acquisition among the cassava value chain actors in Oyo and Ogun States, Nigeria. A multistage sampling technique was adopted in selecting 500 cassava value chain actors which comprise of producers, processors, marketers, and influencers in both Oyo and Ogun States. Primary data were collected on socio-economic characteristics of the respondents, gendered social norms such as information on, financial and material resources, group participation and leadership, technology usage, mobility and division of labour, and gender meta-norms, household characteristics, possession and access to productive assets, access to credit and finance and food insecurity experience. The study employed descriptive statistics, household food insecurity scale, and Poisson regression model in analysing the data collected. The results showed that majority (69.40%) of the respondents in the value chain were females, majority (88%) were married, and had at least primary level of education. The results also showed that common gender norms which restricted women actors in the value chain were norms governing the use of financial resources and relating with extension agents independently from their spouse/partner. Others were: restriction in decision making in groups or organisation, participating in leadership roles, norms on usage of technology, mobility and division of labour. Furthermore, decision-making on major expenditures, control of spouse's assets after death, performing household chores, childcare, and paid work outside the home were prevalent for women in the value chain. Food insecurity was found to be present in the study area, as 67% of the respondents experience little food to eat, 70% could not access healthy and nutritious food, and 48% were hungry and did not eat. Majority (82%) owned agricultural land, 93% possessed non-mechanized farm equipment, 88% had small consumer durables, and 96% owned cell phones. However, ownership of large livestock (11%) and mechanized farm equipment (12%) were relatively low. Additionally, a large percentage of respondents (76%) owned houses or buildings, 71% had large consumer durables, and 50% possessed non-farm business equipment, highlighting their importance. Ownership of other land (68%) and means of transportation (57%) were also noteworthy, reflecting diverse asset acquisition among the respondents. The Poisson regression analysis showed that gender norms have a negative effect on food security (-0.007) and asset acquisition (-0.011) among cassava value chain actors. The study concluded that there were negative effects of gender norms on food security and asset acquisition among cassava value chain actors.